2014
DOI: 10.1245/s10434-014-3545-5
|View full text |Cite
|
Sign up to set email alerts
|

Anaplastic Thyroid Carcinoma: A 25-year Single-Institution Experience

Abstract: In patients with locoregional limited disease, multimodality treatment with gross total surgical resection and postoperative radiotherapy with or without chemotherapy offers the best local control and DSS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
0
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 38 publications
5
61
0
4
Order By: Relevance
“…Several retrospective studies have demonstrated significant survival benefit for ATC patients treated with a multimodal approach (Haymart et al 2013, Mohebati et al 2014, Wendler et al 2016. In an analysis of the Memorial Sloan Kettering Cancer Center, New York, 95 ATC patients treated between 1985 and 2010 were included.…”
Section: Multimodal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…Several retrospective studies have demonstrated significant survival benefit for ATC patients treated with a multimodal approach (Haymart et al 2013, Mohebati et al 2014, Wendler et al 2016. In an analysis of the Memorial Sloan Kettering Cancer Center, New York, 95 ATC patients treated between 1985 and 2010 were included.…”
Section: Multimodal Therapymentioning
confidence: 99%
“…In an analysis of the Memorial Sloan Kettering Cancer Center, New York, 95 ATC patients treated between 1985 and 2010 were included. Patients who had surgery, radiotherapy and/or chemotherapy had 42% 1-year disease-specific survival (DSS) compared to patients without surgery or surgery alone, showing only 6% 1-year DSS (Mohebati et al 2014). In contrast, an analysis of 2742 ATC patients diagnosed between 1998 and 2008 (US National Cancer Database) showed only marginal treatment benefit: median survival rates in patients receiving multimodal treatment ranged between 11.2 months in stage IVA patients, 9.9 months in stage IVB patients and 4.9 months in stage IVC patients (Haymart et al 2013).…”
Section: Multimodal Therapymentioning
confidence: 99%
“…Intensity-Modulated Radiation Therapy has shown better results with reduced toxicity [6]. Chemoradiation has been shown to be superior to radiation alone [7,8]. The recommended chemotherapeutic agents are doxorubicine alone or a combination of drugs in patients with good performance status who desire aggressive therapy.…”
Section: The Current Standards Of Multimodal Therapymentioning
confidence: 99%
“…A recent retrospective review of 95 patients at a tertiary cancer center highlights the prognostic factors and outcomes associated with ATC [8]. More than 65% of the patients were over the age of 65 years, with 50% of patients having concurrent or previous history of differentiated thyroid cancer.…”
Section: The Current Standards Of Multimodal Therapymentioning
confidence: 99%
“…These undifferentiated tumours are extremely aggressive, recurring both locally and distantly. Radiotherapy decreases local recurrence, reduces the morbidity associated with atc progression, and might increase cancer-specific survival [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%